The Implementation of Hybrid Learning Approach in English for Business Communication in Indonesian Vocational Higher Education - MUSDARIAH, Andi (Research and Innovation in Applied Linguistics, 2023)
This article investigates the implementation of hybrid learning in Business Communication at the vocational education level. The study adopts a virtual case study approach utilizing digital narrative inquiry to collect data on teachers' strategies for hybrid learning aimed at enhancing students' business communication performance. Findings reveal that one teacher successfully developed a self-initiated hybrid learning model during explorations in this field. The teacher integrated traditional instruction with diverse online platforms likeMoodle, web-cloud video conferencing, Google Classroom, and social media platforms such as Facebook and WhatsApp to teach English for business communication. In contrast, other teachers demonstrated limited implementation of hybrid learning. Notably, the level of hybrid learning implementation was significantly linked to students' business English performance outcomes. Greaterutilization of hybrid learning strategies correlated with improved student performance in business communication. The research carries implications for pedagogy, underscoring the significance of employing diverse hybrid learning strategies in English teaching.